Debtor nation : the history of America in red ink - Hyman, Louis, 1977- (Politics and society in twentieth-century America., 2011)
Before the twentieth century, personal debt resided on the fringes of the American economy, the province of small-time criminals and struggling merchants. By the end of the century, however, the most profitable corporations and banks in the country lent money to millions of American debtors. How did this happen? The first book to follow the history of personal debt in modern America, Debtor Nation traces the evolution of debt over the course of the twentieth century, following its transformation from fringe to mainstream--thanks to federal policy, financial innovation, and retail competition.